New Observational Constraints on Warm Rain Processes and Their Climate Implications - Xiquan Dong; Peng Wu; Yuan Wang; Baike Xi; Yiyi Huang (Geophysical Research Letters)
Abstract Low stratiform clouds have profound impacts on the hydrological cycle and the Earth’s radiation budget. However, realistic simulation of low clouds in climate models presents a major challenge. Here we employ the newly retrieved cloud and drizzle microphysical properties to improve the autoconversion and accretion parameterizations in a microphysical scheme. We find that the new autoconversion (accretion) rate contributes 14% lower (greater) to total drizzle water content than the original scheme near the cloud top. Compared to satellite results, the simulated cloud liquid water path (LWP) and shortwave cloud radiative effect using the original scheme in a climate model agree well on global average but with large regional differences. Simulations using the updated scheme show a 7.3% decrease in the light rain frequency, and a 10% increase in LWP. The updated microphysics scheme alleviates the long‐lasting problem in most climate models, that is “too frequent and too light precipitation.”